2006
DOI: 10.1111/j.1600-0501.2005.01220.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐grafted sinus implants in periodontally compromised patients: a time‐to‐event analysis

Abstract: This study reports the results of implant therapy involving a sinus membrane lift and of conventional implant therapy in 68 periodontally compromised patients treated between June 1990 and June 2002. Patients had at least two implants inserted, one of which was placed in the maxillary sinus region following fenestration of the lateral sinus wall and lifting of the sinus membrane. Two implant systems were used: a two-stage system (Astra) and a one-stage system (ITI). Annual follow-up visits included recording o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
65
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 45 publications
10
65
1
2
Order By: Relevance
“…Cells derived from different sources have different characteristics [3], so in an effort to foster a more uniform characterization of MSC across different tissue sources and various culture conditions, the International Society for Cellular Therapy (ISCT) has proposed a set of minimal criteria to define MSCs [31,51,52]. In the present study, the surface marker expression of hESMSCs was shown to be in conformity with the criteria mentioned above.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Cells derived from different sources have different characteristics [3], so in an effort to foster a more uniform characterization of MSC across different tissue sources and various culture conditions, the International Society for Cellular Therapy (ISCT) has proposed a set of minimal criteria to define MSCs [31,51,52]. In the present study, the surface marker expression of hESMSCs was shown to be in conformity with the criteria mentioned above.…”
Section: Discussionsupporting
confidence: 77%
“…In bone tissue engineering, cell sheets could act as periosteum, which can provide osteoprogenitor cells and nutrients to the bone defect, thus contributing to regeneration of the host tissue [30]. In the meantime, a clinical study showed that the maxillary sinus lifting resulted in bone augmentation, suggesting that the sinus membrane may function like a periosteum [31]. Although mucosa of both ethmoid sinus and maxillary sinus are sources of cells of osteogenic differentiation potential [10,32], cells from ES have higher colony-forming potential and proliferation capability than cells from MS [10].…”
Section: Introductionmentioning
confidence: 98%
“…The native osteogenic activity associated with the Schneiderian membrane shown by these experiments correlates well with clinical observations of bone formation in sinus lifting procedures without grafting bone substitutes 10,26 . Several studies have shown that mechanical stimulation of the periosteum can also elicit the latent osteogenic capacity of the periosteum in various clinical settings 16,17,28,32 and recently in calvaria and in mandibular periostea in minipigs and in rabbits, respectively 6,20 .…”
Section: Discussionsupporting
confidence: 63%
“…The most commonly used technique to reconstruct the posterior region of the maxilla is augmentation of the maxillary sinus floor, a technique introduced by BOYNE & JAMES and modified by TATUM and by WOOD & MOORE, in which different osteoconductive materials (bone substitutes) were placed between the host bone and the sinus membrane to allow the insertion of dental implants 4,33,36 . Recent clinical studies described a surgical technique combining an open controlled sinus membrane lifting procedure with immediate installation of dental implants that resulted in bone formation only by simple elevation of the maxillary Schneiderian sinus membrane (MSSM) without any adjunctive graft materials 9,10,16,17,22,26,28,32,35,36 .…”
mentioning
confidence: 99%
“…Actualités Odonto-Stomatologiques n°237, mars 2007 dents de sagesse [2] ou de la pose d'implants [3,4] . La consolidation osseuse est particulièrement concernée et se fait trois fois plus souvent avec retard.…”
unclassified